К анализу понятия биологической продуктивности животных - Шпет, Г.И. (Вестник зоологии, 1968)
A comparative potential productivity of animal species is considered as their pro-perty for increasing the biomass of the body in themselves and in their offsprings. Productivity is determined in absolute values (e. q. kg) the progression of reproduction and weight of an adult individual being taken into account. The factors of general productivity of the species is given; its productivity in ontogeny is marked out. Examples are presented of contradictory significance of some productivity factors (growth rate, fertility etc.) even in one species. A comparative productivity of two species can change in the course of time. Estimating the advantages of the compared species, it is necessary to take into consideration the productivity in time unit per space unit because small species are often very productive, but require great areas for settling. Acceleration of growth and productivity increase play a great part in life, natural selection and evolutionary development of animals.